Recognising the challenges of implementing multi-centre adaptive plan of the day radiotherapy. (March 2022) - Webster, Amanda; McNair, Helen A.; Hansen, Vibeke N.; Lewis, Rebecca; Patel, Emma; Miles, Elizabeth; Hall, Emma; Hafeez, Shaista; Huddart, Robert; ,
Highlights: The challenges for 35 radiotherapy centres introducing plan of the day were collated. Challenges arose in all areas of the radiotherapy pathway. Compliance with a protocol must be achieved so adaptive approaches achieve their aim. Both training and monitoring the introduction of plan of the day are recommended. Abstract: Two multicentre adaptive radiotherapy trials utilising Plan of the Day (PoD) with a library of plans were introduced in 35 centres. The common issues that arose from all centres when introducing PoD were collated retrospectively, through reviewing the data pertaining to the pre-trial and on-trial quality assurance programme. It was found that 1, 295 issues arose when introducing PoD in outlining, planning, treatment delivery i.e., PoD selection, and in the overall process of delivering PoD. There was no difference in the number of issues that arose from pre-trial to on-trial. Thus, it is recommended that the implementation of PoD is supported by guidance, reviews, and continuous monitoring.